Role of Remuneration and Board Characteristics for Bank Performance A Study Based on Conventional and Islamic Banking Comparison (KASBIT Business Journal, 2019)
The standing study tried to analyze the role of board remuneration and board characteristics on the comparative performance of commercial and Islamic banking in Pakistan for the duration of 2006 to 2017. The data was collected in panel form for five leading conventional banks and five Islamic banks. Panel estimation techniques like fixed, random and pooled Ordinary least square were applied after conforming Hausman specification test and LM test. Using ROE and ROA, found that Director’s Remuneration is positively and significantly affecting banking performance while Account holder’s investment is positively and significantly affecting bank’s performance for conventional banks only and Social contribution is significantly and positively affecting Islamic banking performance in Pakistan. Using Tobin’s Q as a proxy of market performance indicates remuneration is negatively affecting conventional banking performance while Islamic banking market performance is negatively and significantly affected by board’s composition and positively and significantly affected by social contribution. The policymakers should enhance the remuneration of their directors so as to boost their bank’s performance. Moreover, the management of conventional banks should also consider the account holder’s investment to enhance the accounting performance of their banks. The policymaker in Islamic banks can increase their performance (accounting as well as market) by enhancing the social contribution like Zakat. The discoveries of this comparative study are restricted to the banking sector of Pakistan.
Keywords: Board remuneration; board characteristics; bank performance; panel data modelling; islamic banks of Pakistan